ANALYZING EMPLOYABILITY COMPETENCY: IMPACT OF QUADRUPLE HELIX MODEL TO PROSPECTIVE GRADUATES - Hazmilah, H.; Zanariah, J; Norida, A.; Noraini, S.; Hanipah, H. (PEOPLE: International Journal of Social Sciences, 2016)
Although many employability competencies program are conducted by universities and supported by government employability related policies with the community involvement, all the initiatives have yet to fulfill expectation of employers. The objective of this study was to analyze the impact of quadruple helix model to prospective graduates. The employability skills and quadruple helix model were used as research framework. The degree to which prerequisite of foundation knowledge and skill obtainable through higher education institution, industrial training, the government policies and community initiatives might influence prospective graduates’ employability competencies. This study utilized a quantitative approach through questionnaires adopted from Engineering Accreditation Council (EAC) consist of 10 item scale of engineering employability skill and 23 item of CAAS measurement scale. Reliability and descriptive analysis were used to verify the factor structures that shaped the graduates employability competencies and career adaptability. The results indicated that respondents were in conformity on how higher education program, industry internship program, government policies and community enhancement program influenced their employability competency. Future study should focus on examining systematic changes in factors affecting employability competency for human capital sustainability.